Pengaruh Motivasi Kerja, Pengalaman Kerja, dan Lingkungan Kerja terhadap Prestasi Kerja pada PT Asabri (Persero) Palembang - Eki Ayu Safitri; Fauziah Afriyani; Shafiera Lazuarni (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to find out whether motivation, experience, and the workplace environment have a positive and significant impact on employee performance at PT Asabri (Persero) palembang branch office. The population studied were employees at the palembang branch office of PT Asabri (Persero). The sampling technique used was saturated sampling with a total of 39 respondents. The research method used is multiple linear regression analysis. The results of the research and hypotheses show that motivation, experince, and environment partially or simultaneously have a positive and significant impact on employee performance.